Brazilian business cycles and growth from 1850 to 2000 - Araújo,Eurilton (2008)
We study the cyclical and growth properties of Brazilian per capita output from 1850 to 2000. We find that, contrary to some developed countries, Brazil did not experience large changes in the volatility of per capita output. However, we obtained evidence that the oscillations in economic activity became more persistent after World War II.